Analisis Variabel Yang Mempengaruhi Harga Saham Syariah Di Jakarta Islamic Index - Lisa Febriani (Jurnal Ekonomi, 2019)
One of the methods used by companies to obtain company capital is by selling shares to the public through the capital market. Stock prices can change and this is changed by various factors. This study aims to determine the effect of Debt to Equity Ratio (DER), Earning per Share (EPS), and Return on Equity (ROE) on sharia stock prices listed in the Jakarta Islamic Index (JII) in 2014-2017, both partially and simultaneously. The data used in this study is secondary data are taken from the Indonesia Stock Exchange website (www.idx.co.id), which is in the form of a company's annual financial report. The analysis technique used in this study uses Linear Regression Analysis. Based on the research results, it is known that partially DER has no significant effect on stock prices, while EPS and ROE have a significant effect on stock prices. Simultaneously, DER, EPS, and ROE significantly influence stock prices.